PEMANFAATAN STEEL SLAG INDONESIA DI BIDANG PERTANIAN - Suwarno Suwarno (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2010)
Steel slag is by-product formed in the process of steel manufacturing. In Europe, USA, Japan, China, Korea, and Hawai steel slag has been utilized in agriculture as a liming material for improving acid soil or as Si source for paddy rice and sugar cane plants. Currently, Indonesia produces annually about 540,000 ton of electric furnace (EF) – one kind of steel slag; however none of this is being used in agriculture. Results of researches indicated that Indonesian steel slag could be utilized as a liming material, Si source, as well as peat soil amendment. As a liming material, effect of Indonesian steel slag on growth of plant was slightly better than those of calcite and dolomite. In combination with phosphatic guano, Indonesian steel slag increased effectiveness of phosphatic guano for direct application as P fertilizer. Phosphatic guano was significantly more effective when it was combined with steel slag than be combined with dolomite or calcite. As Si source for paddy rice plant, Indonesian steel slag improved growth and yield of paddy rice both grown on mineral soil containing low available Si on peat soil. The effect of Indonesian steel slag on paddy rice grown on peat soil was significantly better than that of on mineral soil. As peat soil amendment, Indonesian steel slag enhanced growth and bole volume of Acacia cracicarpa grown on peat soil. Keywords: agriculture, Indonesian steel slag, utilization